Crude extracts, flavokawain B and alpinetin compounds from the rhizome of Alpinia mutica induce cell death via UCK2 enzyme inhibition and in turn reduce 18S rRNA biosynthesis in HT-29 cells - Malami, Ibrahim; Abdul, Ahmad Bustamam; Abdullah, Rasedee @ Mat; Kassim, Nur Kartinee; Rosli, Rozita; Yeap, Swee Keong; Waziri, Peter Maitalata; Etti, Imaobong Christopher; Bello, Muhammad Bashir (Public Library of Science, 2017)
Uridine-cytidine kinase 2 is an enzyme that is overexpressed in abnormal cell growth and its implication is considered a hallmark of cancer. Due to the selective expression of UCK2 in cancer cells, a selective inhibition of this key enzyme necessitates the discovery of its potential inhibitors for cancer chemotherapy. The present study was carried out to demonstrate the potentials of natural phytochemicals from the rhizome of Alpinia mutica to inhibit UCK2 useful for colorectal cancer. Here, we employed the used of in vitro to investigate the effectiveness of natural UCK2 inhibitors to cause HT-29 cell death. Extracts, flavokawain B, and alpinetin compound from the rhizome of Alpinia mutica was used in the study. The study demonstrated that the expression of UCK2 mRNA were substantially reduced in treated HT-29 cells. In addition, downregulation in expression of 18S ribosomal RNA was also observed in all treated HT-29 cells. This was confirmed by fluorescence imaging to measure the level of expression of 18S ribosomal RNA in live cell images. The study suggests the possibility of MDM2 protein was downregulated and its suppression subsequently activates the expression of p53 during inhibition of UCK2 enzyme. The expression of p53 is directly linked to a blockage of cell cycle progression at G0/G1 phase and upregulates Bax, cytochrome c, and caspase 3 while Bcl2 was deregulated. In this respect, apoptosis induction and DNA fragmentation were observed in treated HT-29 cells. Initial results from in vitro studies have shown the ability of the bioactive compounds of flavokawain B and alpinetin to target UCK2 enzyme specifically, inducing cell cycle arrest and subsequently leading to cancer cell death, possibly through interfering the MDM2-p53 signalling pathway. These phenomena have proven that the bioactive compounds could be useful for future therapeutic use in colon cancer.